PRAKTIK DAN PENYULUHAN PENGOLAHAN SAWI HIJAU MENJADI STICK SAWI YANG MEMILIKI NILAI EKONOMIS TINGGI DI DESA PAOK PAMPANG KECAMATAN SUKAMULIA - Jannah, Ika Wardiatul; Rahmatillah, Siti; Fasiha, Baiq Nurul; Sulistini, Baiq Laili; Purwati, Lulu; Ayuningsih, Febi; Royani, Alfi; Juniansyah, Ajzun Dwiki; Pratama, Muh Fauzan; Mubin, Hakkul (Universitas Mataram, 2024)
Paok Pampang Village, established as a result of the division from Dasan Lekong Village in 2010, possesses abundant natural resources in agriculture, livestock, and plantations. Agriculture in this village produces various types of food crops and fruits, with green mustard (sawi) being the main commodity. Despite the abundant production of green mustard, its market value remains low due to a lack of product diversification. To enhance its value, an innovation was introduced by processing green mustard into a snack product called